ANTIMICROBIAL POTENTIAL OF HYDROGEL INCORPORATED WITH PLGA NANOPARTICLES OF CROSSANDRA INFUNDIBULIFORMIS - Jyothi, Divya; Priya, Sneh; James, Jainey P (International Journal of Applied Pharmaceutics, 2019)
Objective: Present study is aimed at formulation of Hydrogel containing Poly Lactic Glycolic Acid (PLGA) nanoparticles incorporated with ethanolic extract of Crossandra infundibuliformis (EECI) and investigate the efficacy of hydrogel nanoparticles as a carrier of antimicrobial constituents. Methods: Poly Lactic Glycolic Acid (PLGA) nanoparticles containing ethanolic extract of Crossandra infundibuliformis (EECI) were synthesized by an emulsion-evaporation method and their physicochemical properties were studied. Polymeric PLGA nanoparticles were then incorporated into gel matrix, using Hydroxy Propyl Methyl Cellulose (HPMC K4M) as a base. The antibacterial activity of nanoparticulated hydrogel formulations were evaluated by agar well diffusion method against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa. Results: Nanoparticulate hydrogel formulations exhibited high viscosity, neutral pH with good spreadability which is appropriate for transdermal application as well as showed prolonged drug release from optimized formulation up to 24 h. Nanoparticulate hydrogel formulations were effective inhibitors of all the micro-organisms with more promising activity against Staphylococcus aureus. Conclusion: Nanoparticulate hydrogel formulation can be used as a feasible alternative to conventional formulations of Crossandra infundibuliformis extract with advanced permeation characteristics of antimicrobial constituents for transdermal application.